The Utility of Meditation and Mindfulness-Based Interventions in the Time of COVID-19: A Theoretical Proposition and Systematic Review of the Relevant Prison, Quarantine and Lockdown Literature. Issue 2 (April 2023) - Bursky, Mikell; Kosuri, Mahathi; Walsh Carson, Kaitlin; Babad, Sara; Iskhakova, Alexandra; Nikulina, Valentina
As of July 20, 2021, Covid-19 has killed 4, 086, 000 people, infected at least 190, 169, 833 others, and devastated the world's economy. To slow the spread of the virus, numerous governments instituted "lockdown" policies and quarantines, limiting social interactions to the immediate household. The experience of isolation and uncertainty have contributed to increased fear, anxiety, and loneliness; with limited options of research-supported interventions. Although different in nature, the experiences of quarantine and lockdown have been likened to incarceration. Past research has found meditation and mindfulness-based interventions (MBIs) to be effective psychological treatments for prisoners and may therefore translate well into effective methods for the maintenance of psychological well-being for individuals quarantined during the pandemic. More recently, research investigating the effects of meditation and MBIs during the pandemic have demonstrated preliminary evidence for beneficial psychological improvements. In accordance with the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA), the current narrative review paper: 1) examines the parallels and differences between the experience of quarantine and imprisonment, 2) investigates the mechanisms through which meditation and mindfulness enact their effects, and 3) systematically reviews literature on the benefits of various types of meditation and MBIs for inmates and individuals in lockdown or quarantine. With this knowledge, the public can garner applicable insight into the potential use of meditation and MBIs for individuals forced to cope with pandemic lockdowns and quarantines. Two hundred and twenty one (221) articles were identified through Pubmed and Google Scholar, and 24 articles were ultimately included in the manuscript.